2014
DOI: 10.3748/wjg.v20.i42.15467
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus-mediated angiogenesis: Molecular mechanisms and therapeutic strategies

Abstract: Angiogenesis is an essential process for organ growth and repair. Thus, an imbalance in this process can lead to several diseases including malignancy. Angiogenesis is a critical step in vascular remodeling, tissue damage and wound healing besides being required for invasive tumor growth and metastasis. Because angiogenesis sets an important point in the control of tumor progression, its inhibition is considered a valuable therapeutic approach for tumor treatment. Chronic liver disease including hepatitis C vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 83 publications
2
9
0
Order By: Relevance
“…These findings suggest that both structural and non‐structural regions of HCV genome may trigger angiogenesis by the stimulation of Ang2 synthesis. These data are consistent with earlier studies that reported the important role of Core and NS5A in stimulating the production of several key factors involved in fibrosis (TGF‐β) and angiogenesis (VEGF) through multiple signalling pathways, including PI3K, JNK/p38 and ERK . Also, other studies have described that the structural proteins E1 and E2 may be implicated in pathological regenerative angiogenesis …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings suggest that both structural and non‐structural regions of HCV genome may trigger angiogenesis by the stimulation of Ang2 synthesis. These data are consistent with earlier studies that reported the important role of Core and NS5A in stimulating the production of several key factors involved in fibrosis (TGF‐β) and angiogenesis (VEGF) through multiple signalling pathways, including PI3K, JNK/p38 and ERK . Also, other studies have described that the structural proteins E1 and E2 may be implicated in pathological regenerative angiogenesis …”
Section: Discussionsupporting
confidence: 93%
“…These pathways contribute to the stabilization and activation of HIF-1α, promoting the expression of many angiogenic factors. 38 In conclusion, this study shows a reasonable relationship between the intrahepatic levels of Ang2 and the progression of…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…167,168 HCV infection can trigger hepatic angiogenesis and HCC growth through HIF-1α and VEGF regulation. 169,170 The VEGF activation can occur through several other cell survival pathways, including PI3K/Akt, ERK1/2, NF-κB, and STAT3, which stabilize HIF-1α. It has been demonstrated that the core protein of HCV can trigger angiogenesis through a mechanism that involves cross-talk between TGF-β2, VEGF, and CD34 expression.…”
Section: Angiogenesismentioning
confidence: 99%